Pengaruh beberapa variabel makro terhadap harga saham perusahaan perkebunan dan pengolahan kelapa sawit - ADHINATA, Irzal ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This research was conducted at the Jakarta Stock Exchange under the title The influence of some macroeconomic variables on stock prices of plantation companies and palm oil cultivation in Indonesia stock exchange. The purpose of this study was to determine the effect of each variable since the current stocks of plantation industries and processing of palm oil are attractive to investors since the selling price of CPO and its derivatives have a high price to international market but there is intervention form the government by applying export tax on fluctuative CPO and its derivative products which depend on the selling price of international market since the government is experiencing interference due to the increased price of domestic cooking oil that was allegedly due to the high international price of CPO on the market thus many companies export their products and cause the interference on product inventory. The imbalance in that supply and demand cause the prices of domestic cooking oil is rising. Considering from the production capacity, at this moment Indonesia is the largest manufacturer of CPO and derivatives products by production capacity up to 21.38 million tons on 2008. This study analyzes the influence of world oil prices, dollar exchange rate fluctuations, interest rate of SBI, CPO export tax fluctuations and the price of world CPO to company stock prices of company of plantations industrial and palm oil cultivation in Indonesia stock exchange by using data that are relevant during the period 2007 -- 2008 with 5 companies that are related to that industry. After that, and regression testing and classical assumption testing are conducted on The data obtained from the study, and can be concluded that at that period the stock price of industrial estates and palm oil processing is influenced by the SBI interest rates and fluctuations in crude palm oil export tax and its derivatives.